Sustainability Reporting and Financial Performance of Listed Consumer Goods Firms in Nigeria - Umar, Maryam Mohammed; Mustapha, Lateef Olumide; Yahaya, Onipe Adabenege (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The non-compliance by firms on sustainable development gave rise to climate degradation and ozone layer depletion. The resultant consequences include pollution, habitat loss, and overexploitation of species and the spread of invasive genes. Yet, very few empirical studies have examined the effects of these on corporate performance. In view of this scenario, this study assesses the effects of sustainability reporting on the financial performance of 26 listed consumer goods firms in Nigeria. The correlational research design was adopted for the study, and secondary data were collected from the annual reports and accounts of the firms for a period of 10 years (2009-2018). Multiple regression techniques used to analyse the data and diagnostic checks and post estimation tests were carried out on the data. The results show that social performance has a significant positive effect on financial performance. Similarly, results show that environmental performance has a significant positive effect on financial performance. However, results show that economic performance has a significant negative effect on financial performance. The study concludes that sustainability reporting is important to corporate financial performance. The study, among others, recommends that management should disclose more social and environmental performance activities and less economic performance activities.